Can a Hybrid Method Improve Equity Valuation? An Empirical Evaluation of the Ohlson and Johannesson (2016) Model - Gao, Zhan; Myers, James N.; Myers, Linda A.; Wu, Wan-Ting (The Accounting Review, 2019)
ABSTRACT This paper investigates the validity and usefulness of “hybrid” valuation models. We recast the model in Ohlson and Johannesson (2016) as a hybrid of the Dividend Discount Model and an earnings-based price multiple model, and develop a new hybrid model that generalizes the Residual Income Valuation Model. After validating the theoretical properties of these models' unique parameters, we assess the usefulness of the hybrid models in two applications. In application one, we find that intrinsic values from the hybrid models are more accurate than those from common discounted models or price multiple models. These improvements are attributable to the hybrid models' ability to incorporate stock price and more realistic assumptions about growth. In application two, we find that the implied cost of equity from the hybrid models better captures systematic risks and key idiosyncratic risks, and captures expected returns. These results demonstrate the validity and usefulness of hybrid valuation models. JEL Classifications: G12; G14; G17; G31; M41. Data Availability: The data used are publicly available from the sources cited in the text.